Using spatial games to model and simulate tomato spotted wilt virus-western flowers thrip dynamic system. (2nd October 2018) - Kuang, Yan; Ben-Arieh, David; Zhao, Songnian; Wu, Chih-Hang
Abstract: Modeling a complex chain-effect of biological agents is of great interest to researchers and practitioners. The paper presents such a chain consisting of the tomato spotted wilt virus (TSWV) which is carried by the western flower thrips (WFT) as its host, and infects tomato plants among others. The TSWV is a virus that infects more than 1000 plant species, including agronomic and ornamental crops as well as weed hosts, causing significant financial loss. This virus is transmitted by thrips, and the WFT ( Frankliniella occidentalis ) are reported to be the most important vector due to its wide distribution. Currently, there are mathematical models describing this dynamic system, allowing quantitative analysis of this complex system. This paper introduces a new modeling approach based on a spatial game to model this dynamic system. The paper presents this approach along with simulations and validation using experimental data. This method has a broad descriptive power and is applicable to other vector-borne disease systems.